An analytic approach for resource efficient parametric simulation of electronic circuits. Issue 1 (2nd January 2020) - Schenk, Mario; Muetze, Annette; Krischan, Klaus
ABSTRACT: We propose a resource efficient precision transient circuit simulator approach without time step for solving the systems of differential equations. The method is notably suitable for optimization and worst-case dimensioning of small-scale electronic circuits. A closed-form analytic solution is computed for each of the electronic circuit states. Numerical integration is not required, and therefore, convergence problems are eliminated. An electronic circuit with only linear elements, for example, R, C, L and independent current, and voltage sources (LTI), is described with a system of differential (state) equations. Nonlinear elements, such as L ( i), C ( u ), Diodes, MOSFETs, BJTs and/or PWM controllers are described with piecewise-linear models. Connecting linear and linearized nonlinear elements, results in a linear system of differential equations.